Kinerja Kelembagaan Pnpm-Mpd Dalam Manajemen Bantuan Modal Usaha Petani Miskin Di Kecamatan Seko Kabupaten Luwu Utara Propinsi Sulawesi Selatan - Idris, Ita Purnamasari (AGROTEKBIS, 2013)
Rural PNPM Mandiri (PNPM-MPd) in principle is the welfare of the poor and rural employment opportunities independently through increased community participation (especially the poor, women's groups and community / marginalized groups). This study aims to measure institutional performance (PNPM-MPd) in the management of venture capital support poor farmers. The research was conducted in the Seko Luwu Northern District of South Sulawesi province. Take as many (26 respondents) by using simple techniques claster sampling the importance of the 3 villages namely, medieval village, and village the farthest village from District Seko. In addition to determining the respondents also used purposive technique. Based on the results of research that PNPM-MPd institutional performance shows that the institutional performance PNPM-MPd is 88.46% which shows high institutional performance criteria.